Efforts To Improve The Learning Outcomes Of Students' IPS Using Problem Based Learning Models - Ulfia Trisna; Syarifah Balkis; Suyuti Suyuti (Universitas Negeri Makassar, 2022)
The research was carried out aimed at improving learning outcomes through the application of the Problem based Learning learning model in sosial studies subjects at SMP Negeri 8 Tanjungpinang. Based on the results of previous observations, learning is still teacher-centered, the lack of activeness of students in learning so that it has an impact on the low learning outcomes of students in sosial studies subjects. The subjects of this study were class VII students, totaling 16 people. This study uses a Problem Based Learning learning model, by orienting students to contextual problems to analyzing and evaluating problem solving activities, thereby increasing student activity in sosial studies learning, having an impact on increasing the average value of student learning outcomes with an average score. class average is 75.65 and the percentage of completeness is 87.5%. The data collection instruments used were test instruments and observation sheets. The results of the study indicate that the Problem Based Learning learning model can improve student learning outcomes in sosial studies learning at SMP Negeri 8 Tanjungpinang.